Strategi Kurikulum Pendidikan Islam Dalam Era Pendidikan Modern Sebagai Solusi Terbaik Membentuk Generasi Unggul - Raihani Aththahirah; Harahap, Resmi Rohima; Aghisna Rahmatika W; Ahmad Sabri; Rulli Hidayatullah (Journal Education Innovation (JEI), 2024)
Curriculum Islamic education in modern education is crucial in the best solution in forming a very superior generation. The aim of this research is to provide a strategy on the curriculum of Islamic Education in modern Education that can provide the best solution to form the superior generation. This research uses qualitative research methods using a library research approach. The data obtained includes articles in journals, E-books, websites and other internet media as well as research publications indexed by Google Scholar. The research results show some strategies on the curriculum of Islamic Education in Modern Education that can provide the best solutions for forming a superior generation in the educational curricula of Islam in modern era requires a more dynamic and adaptive curricular strategy so that better educational goals can be achieved and can form a generation or student who is more qualified and superior in the modern era. Furthermore, educational institutions should implement a more generations-centred Islamic curriculum to support the achievement of higher generations. An effective strategy for Islamic educational curricula to form superior generations is as follows: Islamic education should focus on the development of religious and moral values as well as development of science and technology relevant to the needs of society.